MANAJEMEN PENDIDIKAN KARAKTER SISWA DI SEKOLAH DASAR (MGMP PAI Jawa Barat, 2022)
This study aims to find out how to organize and manage and shape the character of elementary school-age children. The research method is descriptive qualitative through observation, documentation and interviews the author tries to examine as deeply as possible about the educational management of elementary school children. The results of this study show that: first, planning has been carried out as well as possible starting from the formulation of objectives, formulation of strategies, determination of policies, mapping of procedures, and improvement of programs; second, the implementation goes well through organizing activities and actions focusing on student character values; third, evaluation of student character education management through activities of supervising the implementation of activities, conducting reflection, analysis and follow-up. Based on the results of research through literature studies, it can be concluded that in shaping the character of a child, a teacher needs to take managerial action so that educational goals that aim to create children with good character can be realized, the elements of planning, (planning), organization (organization), implementation (actuating) and supervision (controlling) are elements that support the implementation of the karate education process for children, especially children of elementary school age.